Rhythm of Love: Patterns of Perception and the Classical Profession of the Hetaira. (2019) - Hullinger, David
Abstract: For a long time, the classical profession of the hetaira, or paid female companion, has eluded definition. The hetaira has often been described as a 'courtesan' and her work as a 'form of prostitution', yet these appellatives often conflict with depictions of the hetaira by classical authors. Accordingly, in this article I will argue that the hetaira was perceived by the Greeks as an elite entertainer whose service of companionship emphasized flirtation and intimacy with a cultivated woman instead of the sale of sex. In order to demonstrate this understanding of the hetaira, I will cite evidence from a wide range of classical writings, particularly legal orations, and will ultimately propose that, when used to indicate a professional, the classical Greek term hetaira should be translated as 'entertainer'.